Dataset from 'Size Distribution of Sperm Whales Acoustically Identified During Long Term Deep-Sea Monitoring in the Ionian Sea' - Caruso Francesco; Sciacca Virginia; Bellia Giorgio; De Domenico Emilio; Larosa Giuseppina; Papale Elena; Pellegrino Carmelo; Pulvirenti Sara; Riccobene Giorgio; Simeone Francesco; Speziale Fabrizio; Viola Salvatore; et al. (Zenodo, 2015)
This dataset is from the study: Caruso Francesco, Virginia Sciacca, Giorgio Bellia, Emilio De Domenico, Giuseppina Larosa, Elena Papale, Carmelo Pellegrino, Sara Pulvirenti, Giorgio Riccobene, Francesco Simeone, Fabrizio Speziale, Salvatore Viola and Gianni Pavan. “Size Distribution of Sperm Whales Acoustically Identified During Long Term Deep-Sea Monitoring in the Ionian Sea.” The archive named NEMO-OvDEDataset.zip contains the results of an automatic analysis developed and applied to the data acquired by theOcean noise Detection Experiment.In detail, a subsample of the large datasetwas processed to assess the size of the recorded sperm whales,by measuring the structure of their acoustic signals. Thedataset consistsin several plots generated by the algorithm described in the cited research article. The files are in PNG format. These data were used to study the size distribution of the sperm whale recorded during the OvDE Passive Acoustic Monitoring. For furtherinformation:riccobene@lns.infn.it(PrincipalInvestigator of theOcean noise Detection Experiment)